Method for detecting water vapor barrier property of lithium battery electrode eardrum

By simulating the heat sealing process of the lithium battery outer material and the eardrum, specific structural samples are prepared and tested, which solves the problem in the existing technology of being unable to effectively detect the water vapor barrier performance of the lithium battery eardrum, and achieves a more accurate performance evaluation.

CN119354846APending Publication Date: 2025-01-24ZHIXIN BOYUAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638470.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art lacks effective detection methods to evaluate the water vapor barrier performance of the eardrum of the lithium battery, which makes it impossible to accurately judge its performance in lithium batteries.

Method used

By simulating the thermal seal processing process of aluminum plastic film and polar eardrum of lithium battery, prepare five -layer structure samples and three -layer structure comparison samples, and perform heat seal, filling and testing. Water vapor barrier performance.

Benefits of technology

This method overcomes the defects that cannot be made into a bag into a bag, which improves the accuracy of the resistance of polar eardrum water vapor resistance, and can more truly simulate the environment of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354846A_ABST
    Figure CN119354846A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery electrode eardrums, and particularly relates to a lithium battery electrode eardrum water vapor barrier property detection method, which comprises the following steps: S1, sample preparation; step S2, heat sealing; step S3, performing filling; step S4, testing; step S5, analyzing; according to the method for detecting the water vapor barrier property of the lithium battery lug membrane, the defect that the lug membrane cannot be made into a bag due to low melting point in direct use of aluminum-plastic membrane detection is overcome by simulating a real heat-sealing process technology of the lithium battery outer packing material aluminum-plastic membrane and the lug membrane and a real use environment of the lithium battery; the water vapor barrier performance of the eardrum is obtained by comparing the test water increment, and the accuracy of the test of the water vapor barrier performance of the eardrum is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery tab films, and in particular relates to a method for detecting water vapor barrier properties of a lithium battery tab film. Background Art

[0002] With the rapid development of the electric vehicle industry in recent years, the technical requirements for lithium-ion batteries, especially power lithium-ion batteries, have been significantly improved, and the industry has put forward more stringent requirements on the moisture control level in the lithium battery process.

[0003] Lithium-ion batteries contain a relatively complex chemical system, and the reaction processes and results of these chemical systems are closely related to water. If the water content is out of control or coarsened, the water content in the lithium-ion battery will exceed the standard, which will further lead to the decomposition of the lithium salt electrolyte, thus adversely affecting the film-forming properties and stability of the positive and negative electrode materials, and ultimately leading to the deterioration of the electrochemical properties of the lithium-ion battery, such as the obvious deterioration of the product capacity, internal resistance, and characteristics, thus leading to the failure of the lithium battery.

[0004] At present, there is only a test method for the water vapor barrier property of aluminum-plastic film, but there is a lack of a test method for the water vapor barrier property of lug film. At the same time, there are significant differences in the materials, functions, etc. of aluminum-plastic film and lug film, and they cannot be converted.

[0005] Therefore, how to overcome the problem that the water vapor barrier property of the tip membrane cannot be effectively detected is a technical problem that urgently needs to be solved in this field.

[0006] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention

[0007] The disclosed embodiments at least provide a method for detecting the water vapor barrier properties of a lithium battery tab membrane.

[0008] In a first aspect, an embodiment of the present disclosure provides a method for detecting the water vapor barrier property of a lithium battery tab film, comprising the following steps: step S1, sample preparation, i.e., cutting a U-shaped tab film to prepare a five-layer structure sample of an aluminum-plastic film, a U-shaped tab film, a Teflon high-temperature resistant gasket, a U-shaped tab film and an aluminum-plastic film stacked in sequence, and a comparison sample of a three-layer structure of an aluminum-plastic film, a U-shaped tab film and an aluminum-plastic film stacked in sequence; step S2, heat sealing, i.e., heat sealing the five-layer structure sample and the three-layer structure comparison sample on three sides, and removing the Teflon high-temperature resistant gasket from the five-layer structure sample after heat sealing to obtain a heat-sealed sample. and comparison heat-sealed samples; step S3, filling, i.e. injecting test liquid into the heat-sealed samples and the comparison heat-sealed samples and sealing them to obtain test samples and comparison test samples; step S4, testing, i.e. performing initial moisture content test and moisture and heat resistance test on the test samples and the comparison test samples respectively to obtain their respective initial moisture content results P1 and moisture and heat resistance moisture content results P2; step S5, analysis, i.e. subtracting P2 from P1 of the test sample to obtain △P1, subtracting P2 from P1 of the comparison test sample to obtain △P2, and then subtracting △P1 from △P2 to obtain △P, which is the increase in moisture of the ear membrane to be tested during the test cycle.

[0009] In an optional embodiment, the size of the U-shaped tab membrane is 55mm*100mm, and the width of the three sides is 10mm.

[0010] In an optional embodiment, the size of the aluminum-plastic film is 55mm*100mm.

[0011] In an optional embodiment, the size of the Teflon high temperature resistant gasket is 35mm*110mm.

[0012] In an optional embodiment, the sample preparation method of the five-layer structure includes: taking a piece of aluminum-plastic film with the heat-sealed surface facing upward, aligning and stacking the cut U-shaped pole ear membranes, and then placing a Teflon high-temperature resistant gasket on the U-shaped pole ear membrane, with a distance of 3-10 mm from the three sides of the U-shaped pole ear membrane, and the other short side is the injection side, and then aligning and stacking another piece of U-shaped pole ear membrane sample, and finally stacking a piece of aluminum-plastic film with the heat-sealed surface facing downward and fixing it to obtain a five-layer structure; wherein the Teflon high-temperature gasket extends out of the injection side by 20 mm.

[0013] In an optional embodiment, the preparation method of the comparison sample of the three-layer structure includes: taking a piece of aluminum-plastic film with the heat-resistant surface facing upward, placing a Teflon high-temperature resistant gasket on the aluminum-plastic film, with a distance of 3-10 mm from the three sides of the aluminum-plastic film, and another short side being the liquid injection side, and then stacking a piece of aluminum-plastic film with the heat-resistant surface facing downward and fixing it to obtain a three-layer structure; wherein the Teflon high-temperature gasket extends out of the liquid injection side by 20 mm.

[0014] In an optional embodiment, the heat sealing temperature is 170-190° C., the heat sealing pressure is 0.3-0.5 MPa, the heat sealing time is 3-5 s, and the heat sealing width is 3-10 mm.

[0015] In an optional embodiment, the test liquid includes any one or more combinations of propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethylene carbonate.

[0016] In an optional embodiment, the amount of the filled test liquid is 1 ml; the sealing position is 50 mm away from the liquid injection edge, the heat sealing temperature is 190° C., the heat sealing pressure is 0.5 MPa, and the heat sealing width is 10 mm.

[0017] In an optional embodiment, the initial moisture content is the moisture content of the test liquid after the test sample and the test comparison sample are left to stand; the moisture and heat resistance moisture content is the moisture content of the test sample and the test comparison sample after being placed in a constant temperature and humidity chamber for 3 days and 7 days; the temperature of the constant temperature and humidity chamber is 80°C and the humidity is 90%.

[0018] The beneficial effect of the present invention is that the method for detecting the water vapor barrier property of the tab membrane of a lithium battery overcomes the defect that the tab membrane has a low melting point and cannot be made into a bag when directly using the aluminum-plastic film for testing by simulating the actual process of heat sealing between the aluminum-plastic film and the tab membrane as the outer packaging material of the lithium battery and the actual use environment of the lithium battery, and the water vapor barrier property of the tab membrane is obtained by comparing the increase in moisture in the test, thereby improving the accuracy of the water vapor barrier property test of the tab membrane.

[0019] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.

[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A schematic diagram of the structure of a U-shaped tab membrane provided in an embodiment of the present disclosure;

[0023] Figure 2 A schematic diagram of a sample structure of a five-layer structure provided in an embodiment of the present disclosure;

[0024] Figure 3 A schematic diagram of a comparative sample structure of a three-layer structure provided in an embodiment of the present disclosure, with a stacking schematic diagram on the left and a heat sealing schematic diagram on the right;

[0025] Figure 4 A schematic diagram of edge sealing of a sample with a five-layer structure provided in an embodiment of the present disclosure.

[0026] In the figure:

[0027] 1. U-shaped ear membrane; 2. Aluminum-plastic film; 3. Teflon high temperature resistant gasket; 4. Heat sealing area. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.

[0030] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0031] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.

[0032] Aluminum-plastic film is mainly used for the outer packaging of soft-pack batteries, which plays a role in protecting the internal structure of the battery and preventing the battery from short circuiting. It is usually composed of multiple layers of materials, including aluminum foil, plastic film, etc., and the layers of materials are bonded together through heat sealing technology to form a sealed packaging structure. The use of aluminum-plastic film can provide good sealing and mechanical protection, and is suitable for battery packaging needs of various shapes and sizes.

[0033] The lug membrane is a key component of lithium batteries. It is located between the positive and negative electrodes of the battery and the external circuit, and serves to connect the internal current collector of the battery with the external circuit. The lug membrane is usually made of conductive materials, has good conductivity and stability, and can ensure the effective transmission of current between the inside and outside of the battery. The design and manufacture of the lug membrane is crucial to the performance and safety of the battery, because it directly affects the charging and discharging efficiency and safety of the battery.

[0034] Since the ear film has a low melting point, if the method of using aluminum-plastic film to block water and heat-seal paper bags is used directly for testing, the ear film alone will easily melt and cannot be made into a bag for testing.

[0035] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.

[0036] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0037] The present disclosure provides a method for detecting the water vapor barrier property of a lithium battery tab film, comprising the following steps: step S1, sample preparation, i.e., cutting a U-shaped tab film to prepare a five-layer structure sample of an aluminum-plastic film, a U-shaped tab film, a Teflon high-temperature resistant gasket, a U-shaped tab film and an aluminum-plastic film stacked in sequence, and a comparison sample of a three-layer structure of an aluminum-plastic film, a U-shaped tab film and an aluminum-plastic film stacked in sequence; step S2, heat sealing, i.e., heat sealing the five-layer structure sample and the three-layer structure comparison sample on three sides, and taking out the Teflon high-temperature resistant gasket from the five-layer structure sample after heat sealing, to obtain a heat-sealed sample and a comparison sample. Heat-sealed sample; step S3, filling, i.e. injecting test liquid into the heat-sealed sample and the comparative heat-sealed sample and sealing them to obtain the test sample and the comparative test sample; step S4, testing, i.e. performing initial moisture content test and moisture and heat resistance test on the test sample and the comparative test sample respectively to obtain their respective initial moisture content results P1 and moisture and heat resistance moisture content results P2; step S5, analysis, i.e. subtracting P2 from P1 of the test sample to obtain △P1, subtracting P2 from P1 of the comparative test sample to obtain △P2, and then subtracting △P1 from △P2 to obtain △P, which is the increase in moisture of the pole ear membrane to be tested during the test cycle.

[0038] In some embodiments, specifically, Figure 1 As shown, the size of the U-shaped tab membrane is 55mm*100mm, and the width of the three sides is 10mm.

[0039] In some embodiments, specifically, the size of the aluminum-plastic film is 55 mm*100 mm.

[0040] In some embodiments, specifically, the size of the Teflon high temperature resistant gasket is 35mm*110mm. The provision of the Teflon high temperature resistant gasket can prevent PP from overmelting and accumulating on the heat sealing edge during heat sealing, thereby affecting the test data.

[0041] In some embodiments, specifically, Figure 2 As shown, the sample preparation method of the five-layer structure includes: taking a piece of aluminum-plastic film with the heat-sealed surface facing upward, aligning and stacking the cut U-shaped pole ear membranes, and then placing a Teflon high-temperature resistant gasket on the U-shaped pole ear membrane, with a distance of 3-10mm from the three sides of the U-shaped pole ear membrane, and the other short side is the injection side, and then aligning and stacking another piece of U-shaped pole ear membrane sample, and finally stacking a piece of aluminum-plastic film with the heat-sealed surface facing downward and fixing it to obtain a five-layer structure; wherein the Teflon high-temperature gasket extends 20mm from the injection side.

[0042] In some embodiments, specifically, Figure 3As shown, the preparation method of the comparative sample of the three-layer structure includes: taking a piece of aluminum-plastic film with the heat-resistant surface facing upward, placing a Teflon high-temperature resistant gasket on the aluminum-plastic film, with a distance of 3-10mm from the three sides of the aluminum-plastic film, and another short side being the injection side, and then stacking a piece of aluminum-plastic film with the heat-resistant surface facing downward and fixing it to obtain a three-layer structure; wherein the Teflon high-temperature gasket extends out of the injection side by 20mm.

[0043] In some embodiments, specifically, the heat sealing temperature is 170-190° C., the heat sealing pressure is 0.3-0.5 MPa, the heat sealing time is 3-5 s, and the heat sealing width is 3-10 mm.

[0044] In some embodiments, specifically, the test liquid includes any one or more combinations of propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethylene carbonate.

[0045] In some embodiments, specifically, the amount of the filled test liquid is 1 ml; the sealing position is 50 mm away from the liquid injection edge, the heat sealing temperature is 190° C., the heat sealing pressure is 0.5 MPa, and the heat sealing width is 10 mm.

[0046] In some embodiments, specifically, the initial moisture content is the moisture content of the test liquid after the test sample and the test comparison sample are left standing; the moisture and heat resistance moisture content is the moisture content of the test sample and the test comparison sample after being placed in a constant temperature and humidity chamber for 3 days and 7 days; the temperature of the constant temperature and humidity chamber is 80°C and the humidity is 90%.

[0047] Example 1

[0048] Step S1, sample preparation, take the tab film sample to be tested, and cut it into a U-shaped sample of 55*100mm; take the auxiliary comparative test aluminum-plastic film sample, and cut it into a single piece of 55*100mm sample; take the Teflon high temperature resistant gasket, and cut it into a single piece of 35*110mm.

[0049] S11 Take a piece of auxiliary test aluminum-plastic film sample with the heat-sealing surface facing upwards, align and stack the cut U-shaped ear film samples, and then place the Teflon high-temperature resistant gasket on the U-shaped ear film sample, with a distance of 10mm from the three sides of the sample. The other short side is the liquid injection side. The Teflon high-temperature gasket needs to extend 20mm to facilitate the removal of the gasket after heat sealing. Then align and stack another piece of U-shaped ear film sample, and finally stack the auxiliary test aluminum-plastic film sample with the heat-sealing surface facing downwards and fix it. There are a total of 5 layers of structure to obtain the test sample.

[0050] S12 Take an auxiliary comparison aluminum-plastic film sample with the heat-sealing surface facing upwards, place the Teflon high-temperature resistant gasket on the aluminum-plastic film sample, with a distance of 10mm from the three sides of the sample, and the other short side is the liquid injection side. The Teflon high-temperature gasket needs to extend 15-20mm to facilitate the removal of the gasket after heat sealing. Then stack and fix another auxiliary comparison aluminum-plastic film sample with the heat-sealing surface facing downwards, with a total of 3 layers of structure to obtain a comparison test sample.

[0051] S2: Heat sealing: The test sample and the comparative test sample prepared above are heat sealed on three sides, with the heat sealing temperature being 190° C., the heat sealing pressure being 0.5 MPa, the heat sealing time being 5 s, and the heat sealing width being 10 mm. After the heat sealing is completed, the Teflon high-temperature gasket is removed.

[0052] S3: filling and sealing: dimethyl carbonate, diethyl carbonate and ethylene carbonate are mixed in a molar ratio of 1:1:1, and 1 mole of lithium salt is added to obtain a test liquid. The test sample, comparative test sample and test liquid obtained in S2 and a simple manual edge banding machine are transferred to a glove box. 1 ml of the test liquid is injected into the test sample. After the injection is completed, preheat sealing is performed in the glove box. The temperature of the simple manual edge banding machine is 190°C.

[0053] After the pre-heat sealing is completed, the prepared samples are transferred out of the glove box for final heat sealing. The heat sealing position is 50 mm away from the short side, the heat sealing temperature is 190°C, the heat sealing pressure is 0.5 MPa, and the heat sealing width is 10 mm. Finally, the heat-sealed test samples are obtained. 15 samples need to be prepared in one batch.

[0054] S41: Initial moisture content test: After the test samples and comparative test samples prepared in S3 are allowed to stand for a period of time, 5 samples are randomly selected for initial moisture content test. A corner of the selected samples is cut off, and 0.2 ml of liquid is extracted using a disposable sterile syringe. The test liquid is then tested for moisture using a Karl Fischer moisture tester. Five samples are tested, and the average value of the five points is calculated to obtain the initial moisture content test sample-P1 and the comparative test sample-P1.

[0055] S42: Moisture and heat resistance test: The remaining 10 samples prepared in S3 were placed in a constant temperature and humidity chamber, set at 80°C and 90% humidity. The test cycle was 3 days and 7 days. Five samples were randomly selected for moisture content test in each test cycle, and the average value of the five points was calculated to obtain the moisture content of the test liquid in the test cycle, the test sample-P2, and the comparison test sample-P2.

[0056] S5: Data analysis and evaluation:

[0057] Aluminum-plastic film comparison sample: Subtract P1 obtained by S41 from P2 obtained by S42 to get the increase in moisture content of the aluminum-plastic film comparison sample during the test cycle, △P1;

[0058] Tab membrane sample: Subtract P1 obtained from S41 from P2 obtained from S42 to get the increase in moisture content of the tab membrane sample during the test cycle, △P2.

[0059] Subtract △P1 from △P2 to get △P, which is the increase in moisture in the tab membrane during the test cycle. The water vapor barrier performance of different tab membrane test samples can be evaluated based on the size of △P.

[0060] Example 2

[0061] Specifically, in Example 1, other conditions remain unchanged.

[0062] Specifically, the moisture content performance of the aluminum-plastic film comparison sample, the tab film sample of Example 1, and the tab film sample of Example 2 are shown in Table 1 below.

[0063] Table 1

[0064]

[0065] In summary, the method for testing the water vapor barrier properties of the lithium battery tab film simulates the actual process of heat sealing between the aluminum-plastic film and the tab film, the outer packaging material of the lithium battery, and the actual use environment of the lithium battery, thereby overcoming the defect that the tab film has a low melting point and cannot be made into a bag when the aluminum-plastic film is directly used for testing. The water vapor barrier properties of the tab film are obtained by comparing the increase in moisture in the test, thereby improving the accuracy of the water vapor barrier properties test of the tab film.

[0066] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for detecting water vapor barrier properties of a lithium battery lug membrane, characterized in that: The steps include: Step S1, sample preparation, i.e. cutting the U-shaped tab film to prepare a sample having a five-layer structure of an aluminum-plastic film, a U-shaped tab film, a Teflon high temperature resistant gasket, a U-shaped tab film and an aluminum-plastic film stacked in sequence, and a comparative sample having a three-layer structure of an aluminum-plastic film, a U-shaped tab film and an aluminum-plastic film stacked in sequence; Step S2, heat sealing, i.e. heat sealing the three sides of the five-layer structure sample and the three-layer structure comparison sample, and taking out the Teflon high temperature resistant gasket in the five-layer structure sample after heat sealing, to obtain a heat sealed sample and a comparison heat sealed sample; Step S3, filling, i.e. injecting the test liquid into the heat-sealed sample and the comparative heat-sealed sample and sealing them to obtain the test sample and the comparative test sample; Step S4, testing, i.e., performing an initial moisture content test and a moisture and heat resistance test on the test sample and the test comparison sample respectively, to obtain their respective initial moisture content results P1 and moisture and heat resistance moisture content results P2; Step S5, analysis, that is, subtract P2 from P1 of the test sample to obtain △P1, subtract P2 from P1 of the comparison test sample to obtain △P2, and then subtract △P1 from △P2 to obtain △P, which is the increase in moisture of the electrode ear membrane to be tested during the test cycle.

2. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The size of the U-shaped tab membrane is 55mm*100mm, and the width of the three sides is 10mm.

3. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The size of the aluminum-plastic film is 55mm*100mm.

4. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The size of the Teflon high temperature resistant gasket is 35mm*110mm.

5. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The sample preparation method of the five-layer structure comprises: Take a piece of aluminum-plastic film with the heat-sealed surface facing upward, align and stack the cut U-shaped pole ear membranes, then place a Teflon high-temperature resistant gasket on the U-shaped pole ear membrane, with a distance of 3-10 mm from the three sides of the U-shaped pole ear membrane, and the other short side is the liquid injection side, then align and stack another piece of U-shaped pole ear membrane sample, and finally stack a piece of aluminum-plastic film with the heat-sealed surface facing downward and fix it to obtain a five-layer structure; wherein The Teflon high temperature gasket extends out of the liquid injection edge by 20 mm.

6. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The method for preparing the comparative sample of the three-layer structure comprises: Take a piece of aluminum-plastic film with the heat-sealed surface facing upward, place a Teflon high-temperature resistant gasket on the aluminum-plastic film, with a distance of 3-10 mm from the three sides of the aluminum-plastic film, and the other short side is the liquid injection side, and then stack another piece of aluminum-plastic film with the heat-sealed surface facing downward and fix it to obtain a three-layer structure; wherein The Teflon high temperature gasket extends out of the liquid injection edge by 20 mm.

7. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The heat sealing temperature is 170-190° C., the heat sealing pressure is 0.3-0.5 MPa, the heat sealing time is 3-5 s, and the heat sealing width is 3-10 mm.

8. The method for detecting water vapor barrier properties of a lithium battery tab film according to claim 1, characterized in that: The test liquid includes any one or more combinations of propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethylene carbonate.

9. The method for detecting water vapor barrier properties of a lithium battery lug membrane according to claim 1, characterized in that: The amount of the test liquid filled is 1 ml; The sealing position is 50 mm away from the liquid injection edge, the heat sealing temperature is 190° C., the heat sealing pressure is 0.5 MPa, and the heat sealing width is 10 mm.

10. The method for detecting water vapor barrier properties of a lithium battery tab film according to claim 1, characterized in that: The initial water content is the water content of the test liquid after the test sample and the test comparison sample are left to stand; The moisture and heat resistance water content refers to the water content of the test sample and the test comparison sample after being placed in a constant temperature and humidity chamber for 3 days and 7 days; The temperature of the constant temperature and humidity box is 80° C. and the humidity is 90%.